From nutrition to digestion: a contextualized porposal for the digestive system teaching - Landinho, Flavia Martho [UNESP]; Duarte, Rafael Mendonca [UNESP]; Talamoni, Ana Carolina Biscalquini[UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2022)
Learning about the human body is understanding the functioning of the body itself, considering its biological and sociocultural aspects. However, teaching practices prefer a Cartesian approach in which the body is treated in a reductionist way, restricting it to anatomical and physiological aspects often disconnected. That is the case of the digestive system and the approach to food and nutrition education is considered a contemporary cross-cutting topic by the National Common Curriculum Base. With this in mind, this research surveyed previous conceptions on the guiding theme nutrition with 6th-grade students of elementary school II in Sao Vicente, SP. From there, we develop and apply a didactic sequence to promote anatomical and physiological knowledge of the digestive system from nutrition. Results indicate that after applying the sequence, the students acquired concepts about the morphophysiology of the digestive system, and also, understood that nutrition is guided by sociocultural aspects.
Keywords: Nutrition education; Pedagogical practice; Learning process